From Affective Arrangements to Affective Milieus - Schuetze, Paul (Frontiers in Psychology, 2021)
In this paper, I develop the concept of affective milieus by building on the recently established notion of affective arrangements (Slaby, Mühlhoff, & Wüschner, 2019). Affective arrangements bring together the more analytical research of situated affectivity with affect studies informed by cultural theory. As such, this concept takes a step past the usual synchronic understanding of situatedness towards an understanding of the social, dynamic, historical and cultural situatedness of individuals in relation to situated affectivity. However, I argue that affective arrangements remain too narrow in their scope of analysis, since their focus mainly lies on local, marked-off and unique constellations of affect relations. They neglect the more mundane and day-to-day affect dynamics of social life. Hence, I introduce the notion of affective milieus, which brings to light the everyday, ubiquitous affective engagements of individuals with their socio-material surroundings. Affective milieus specifically call attention to how commonplace affect relations create territories in the social universe which form and mold individuals all the time. In that way, this paper apprehends and advances recent developments in the research on situated affectivity.